Measures of financial risk - Dowd, Kevin (Henry Stewart Talks, 2007)
Nature of financial risk, Representing financial risk using a density function, VaR as a risk measure, Expected shortfall, Coherent risk measures, Worst-case scenario analyses
Archived at 2022/04/04